Tantangan Kualitas Layanan Berbasis Smart City pada Sektor Publik dan Privat - Sholikah, Mar'atus; Harsono, Dwi (Jurnal Penelitian Kesejahteraan Sosial, 2020)
Service based smart city is very crucial to be examined because the features of service products are free and easier to use than traditional. The study aims to determine the difference in service quality based on smart city with conventional. The qualitative method using literature study was used in this study. The technique of data analysis uses content analysis method. Finding of this study are (1) service based on smart city has superior characteristics compared to conventional services, because it is more flexible, elastic, and responsive. Services based on smart city are better able to improve the public service quality, because it utilizes technology based on cloud computing to facilitate and accelerate the flow of information for decision making process. (2) Conventional service quality has different measurement indicators with service quality based on smart city. In conventional service, measurement services quality use the servqual model, while services quality based on smart city implement e-GovQual. (3) The challenge in implementing service based on smart city is the low penetration of ICT, especially in developing countries; fraud in the internet space; the disruption of individual privacy. Therefore, the partnership between public sector, private sector, and civil society is the best ways for the implementation of the service based on smart city. The limitation of this study only discusses the comparison of service quality of smart city and conventional.